PENGARUH KEPUASAN KERJA DAN JOB INSECURITY TERHADAP TURNOVER INTENTION PADA KARYAWAN KONTRAK PT. SINAR PRIMA INDAH - I Putu Agus Sandiyasa; Ni Ketut Murdani; I Nyoman Wahyu Widiana (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to analyze the influence of Job Satisfaction and Job Insecurity on Turnover Intention. The population of this research is contract employees of PT. Sinar Prima Indah in Denpasar. The sampling technique used was a saturated sample, with a total of 50 respondents. The data collection method was carried out using a Likert scale questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study show that job satisfaction has a negative and insignificant effect on turnover intention, while job insecurity has a positive and significant effect on turnover intention. The F test results show an F value of 26.854 and a significance level of 0.000. This means that simultaneously the job satisfaction and job insecurity variables have a significant effect on the employee turnover intention variable. The coefficient of determination test results obtained an R Square value of 0.533. This shows that 53.3% of the results are determined by the variables in this study and the remaining 46.7% are determined by other variables not analyzed in this study.